Importazioni di ceramiche fini orientali ad Aquileia. Nuovi dati dalle collezioni storiche del Museo Archeologico Nazionale - Ventura, Paola; Maggi, Paola (Rei Cretariae Romanae Fautorum Acta, 2022)
Four decades after the identification of Eastern sigillata in Aquileia and in the Northern Adriatic region and the first studies dealing with the trade of tablewares from the Eastern Mediterranean, based on scant items from the museum collections, our knowledge has progressively improved, thanks to the increasing amount of findings from stratigraphic excavation. The analysis of Eastern sigillata and relief pottery recovered in the recently published 2004-2005 excavation of a stretch of Canale Anfora revealed the high occurrence of these productions in the context under review: they prevailed, during some phases, over both Italic and other imports. Aiming to probe this trend and to increase the corpus of published items – pending further editions of the ongoing studies – the systematic recognition of the old collections in the deposits of the National Archaeological Museum of Aquileia was undertaken: they consist of quite a remarkable group of fragments and complete vessels, often lacking provenance data. Corinthian ware and Eastern sigillata were considered: the former is represented by 34 specimens (some of them listed in the catalogue by Daniele Malfitana in 2007), the latter by 33 (only one of them already published), increasing the so far known data-set with no less than 46 items overall and enhancing the knowledge framework to evaluate better the consistency of fine ceramic imports from the East destined for the Upper Adriatic emporium.